Proton-driven Assembly of the Rous Sarcoma Virus Capsid Protein Results in the Formation of Icosahedral Particles - Hyun, Jae-Kyung; Radjainia, Mazdak; Kingston, Richard L.; Mitra, Alok K. (The Journal of biological chemistry, 2010)
In a mature and infectious retroviral particle, the capsid protein (CA) forms a shell surrounding the genomic RNA and the replicative machinery of the virus. The irregular nature of this capsid shell precludes direct atomic resolution structural analysis. CA hexamers and pentamers are the fundamental building blocks of the capsid, however the pentameric state, in particular, remains poorly characterized. We have developed an efficient in vitro protocol for studying the assembly of Rous sarcoma virus (RSV) CA that involves mild acidification and produces structures modeling the authentic viral capsid. These structures include regular spherical particles with T = 1 icosahedral symmetry, built from CA pentamers alone. These particles were subject to cryoelectron microscopy (cryo-EM) and image processing, and a pseudo-atomic model of the icosahedron was created by docking atomic structures of the constituent CA domains into the cryo-EM-derived three-dimensional density map. The N-terminal domain (NTD) of CA forms pentameric turrets, which decorate the surface of the icosahedron, while the C-terminal domain (CTD) of CA is positioned underneath, linking the pentamers. Biophysical analysis of the icosahedral particle preparation reveals that CA monomers and icosahedra are the only detectable species and that these exist in reversible equilibrium at pH 5. These same acidic conditions are known to promote formation of a RSV CA CTD dimer, present within the icosahedral particle, which facilitates capsid assembly. The results are consistent with a model in which RSV CA assembly is a nucleation-limited process driven by very weak protein-protein interactions.